Hirnantian (Ordovician) through Wenlock (Silurian) conodont biostratigraphy, bioevents, and integration with graptolite biozones, Cape Phillips Formation slope facies, Cornwallis Island, Canadian Arctic Islands - Zhang, Shunxin; Jowett, David Martyn Stuart; Barnes, Chris R. (NRC Research Press (a division of Canadian Science Publishing), 2017)
Cornwallis Island in the Canadian Arctic Archipelago provides one of the worldâ s best areas for establishing an integrated graptolite-conodont biozonation for the Late Ordovician-Silurian given the well-exposed interfingering relationship of the basinal shale and carbonate platform facies. Building on earlier graptolite work, 180 samples were collected from nine sections of the Cape Phillips Formation, of which 118 yielded approximately 7600 conodont elements representing 54 species in 25 genera, including one new genus and species, Mayrodus melchini; the conodonts are well preserved with minimal thermal alteration (CAI 1). Nine conodont zones are recognized and defined for this region, namely the Amorphognathus ordovicicus, Distomodus kentuckyensis, Aspelundia expansa, As. fluegeli and Pterospathodus celloni Interval zones, Pt. a. amorphognathoides Taxon-range Zone, Pt. pennatus procerus and Kockelella ranuliformis Highest-occurrence zones, and K. ortus absidata Taxon-range Zone. An integration of graptolite and conodont zones is documented. Earlier paleontological and isotope geochemical studies have demonstrated the dynamic nature of the Silurian ocean-climate system and identified major faunal turnovers or events. Five of these are recognized in the Cornwallis fauna and related to oceanographic and climate changes, in part referring to recent oxygen isotope data from conodonts from the Cornwallis collections: Hirnantian extinction event, Sandvika Event (late Aeronian, Llandovery), Snipklint Primo Episode (early Telychian, Llandovery), Ireviken Event (late Telychian, Llandovery-Sheinwoodian, Wenlock) and Mulde Event (early Homerian, Wenlock). The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.